Makrofol DE 1-4 as alpha dosimeter: Optimum etching conditions. (October 2018) - Rammah, Y.S.; Awad, E.M.; Ashraf, O.
Abstract: A reduction of the detection threshold of Makrofol DE 1-4 to be z / β 40 using normal chemical etching (CE) has been achieved for alpha particles tracks in the energy window 1–5 MeV. Four groups of Makrofol DE 1-4 polycarbonate track detectors of thickness 175 µm have been employed for this purpose. Two groups were exposed to 252 Cf as a source of fission fragments ( ff ) for bulk etch rate determination and the other two groups were exposed to 241 Am as a source of 5.5 MeV alpha particles, whose energy could be reduced by changing the air gap. Irradiated samples of Makrofol DE 1-4 were etched in a mixture of methanol alcohol and NaOH in an aqueous solution of (8 ml of 10 N NaOH + X ml CH3 OH: X = 2 and 3) at 60 °C for different etching times. The fission track diameter, the bulk etch rate, alpha track diameter, detection sensitivity and etching efficiency of the detector were studied. The detector sensitivity and efficiency show the same behavior for all investigated alpha energies and both are independent on methanol concentration in the etching solution. Two optimum etching conditions were obtained for alpha tracks observation are 8 ml of 10 N NaOH + 3 ml CH3 OH at 60 °C for etching time 1.5 h and 8 ml NaOH 10 N + 2 ml CH3 OH at 60 °C with etching time 2 h. These conditions led to lowering the detection threshold of a Makrofol DE 1-4 to z / β 40 for the first time and the detection stopping power threshold to ≈ 170 keV/µm. Alpha particle tracks at the characteristic energy of the Bragg peak region were observed, which confirms the ability of this detector to record alpha particles. Highlights: Low detection threshold for alpha charged particles using Makrofol DE 1-4 of z/β 40 was achieved. The detection stopping power threshold for Makrofol DE 1-4 at ≈ 170 keV/µm was obtained for the first time. Alpha particles with a wider energy range 1-5 MeV were observed in Makrofol DE 1-4 detector. Optimum etching conditions of 8 ml of 10N NaOH + 3 ml CH3 OH at 60 o C for 1.5 h was determined. Detection efficiency of 30-32% at 2 MeV alpha energy with 18.4-25.25 ± 0.22 μm mean track diameter was obtained.